Legal Policy in the Legal System: Concept, Implementation, and Challenges - Bianco, Bento (CV. Green Publisher Indonesia, 2025)
This study aims to design and develop a web-based Human Resources Management (HRM) application to simplify the human resource management process at PT. Perkasa Satria Nusantara. The application development follows the Waterfall model of the System Development Life Cycle (SDLC), which includes planning, analysis, design, implementation, and testing stages. The research uses interviews with a Likert scale to collect data regarding user needs and the HR process in the company. The results show that the developed application improves the efficiency of managing employee data, attendance, and related reports in a more structured and organized manner. This application also facilitates the HR department at PT. Perkasa Satria Nusantara in managing employee data more effectively, reducing manual errors, and speeding up administrative processes. The implications of this research suggest that the web-based HRM application can reduce manual errors, expedite HR administrative management, and support faster and more accurate decision-making. This application is expected to improve the operational efficiency of the company in managing human resources. In the future, this application can be further developed by adding additional features such as recruitment and training management to support the development of human resources in the company.